2016
DOI: 10.1007/s11605-016-3134-y
|View full text |Cite
|
Sign up to set email alerts
|

Population-Based Epidemiology and Mortality of Small Malignant Gastrointestinal Stromal Tumors in the USA

Abstract: Background and Aims Gastrointestinal stromal tumors (GISTs) have significant variability in size and malignant behavior. Our current understanding is limited to pathological analyses, autopsy studies, and small case series. The aim of the current study is to define the risk factors, incidence, and mortality rates of GIST <2 cm in the National Cancer Institute’s Surveillance, Epidemiology, and End Results database. Methods Patients with histologically confirmed malignant GIST <2 cm were studied from 2001 to 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 25 publications
1
47
0
3
Order By: Relevance
“…Moreover, A study from Germany showed among the consecutive 98 autopsy cases, miro-GIST (less than 1 cm) were found in 22 patients (22.5%) [7]. A latest population-Based study [8] for milli-GIST (<2 cm) in the National Cancer Institute’s SEER database showed that the annual incidence rate of gastric milli-GISTs was 2.6 per 10 million.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, A study from Germany showed among the consecutive 98 autopsy cases, miro-GIST (less than 1 cm) were found in 22 patients (22.5%) [7]. A latest population-Based study [8] for milli-GIST (<2 cm) in the National Cancer Institute’s SEER database showed that the annual incidence rate of gastric milli-GISTs was 2.6 per 10 million.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, small bowel GIST tumors show highest incidence among Asian/Pacific Islanders [51]. However, when considering GIST tumors in any part of the gastrointestinal tract, Blacks have highest incidence of all populations [52,53]. …”
Section: Introductionmentioning
confidence: 99%
“…Coe et al published the first population-based analysis of malignant GIST <2 cm throughout the gastrointestinal (GI) tract and identified a mortality risk that has been underappreciated by gastroenterologists, surgeons, and oncologists. 61 In fact, they found that the 5-year GIST-specific mortality rate was 12.9%. Furthermore, 11% of patients with GIST <2 cm had regional or distant metastases.…”
Section: Small Gistmentioning
confidence: 98%